Epidural Neostigmine versus Fentanyl to Decrease Bupivacaine Use in Patient-controlled Epidural Analgesia during Labor: A Randomized, Double-blind, Controlled Study. (July 2017) - Booth, Jessica L.; Ross, Vernon H.; Nelson, Kenneth E.; Harris, Lynnette; Eisenach, James C.; Pan, Peter H.
Abstract : Background: The addition of opioids to epidural local anesthetic reduces local anesthetic consumption by 20% but at the expense of side effects and time spent for regulatory compliance paperwork. Epidural neostigmine also reduces local anesthetic use. The authors hypothesized that epidural bupivacaine with neostigmine would decrease total hourly bupivacaine use compared with epidural bupivacaine with fentanyl for patient-controlled epidural analgesia. Methods: A total of 215 American Society of Anesthesiologists physical status II, laboring parturients requesting labor epidural analgesia consented to the study and were randomized to receive 0.125% bupivacaine with the addition of either fentanyl (2 μg/ml) or neostigmine (2, 4, or 8 μg/ml). The primary outcome was total hourly local anesthetic consumption, defined as total patient-controlled epidural analgesia use and top-ups (expressed as milliliters of 0.125% bupivacaine) divided by the infusion duration. A priori analysis determined a group size of 35 was needed to have 80% power at α = 0.05 to detect a 20% difference in the primary outcome. Results: Of 215 subjects consented, 151 patients were evaluable. Demographics, maternal and fetal outcomes, and labor characteristics were similar among groups. Total hourly local anesthetic consumption did not differ among groups ( P = 0.55). The total median hourly bupivacaine consumption in the fentanyl group was 16.0 ml/h compared with 15.3, 14.6, and 16.2 ml/h in the 2, 4, and 8 μg/ml neostigmine groups, respectively ( P = 0.55). Conclusions: The data do not support any difference in bupivacaine requirements for labor patient-controlled epidural analgesia whether patients receive epidural bupivacaine with 2 to 8 μg/ml neostigmine or epidural bupivacaine with 2 μg/ml fentanyl. Abstract : Adding neostigmine (2, 4, or 8 μg/ml) to bupivacaine for patient-controlled epidural analgesia during labor did not reduce bupivacaine requirement compared with bupivacaine plus fentanyl.